2014
DOI: 10.1098/rspb.2014.1420
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific divergence and convergence of floral tube length in specialized pollination interactions

Abstract: Floral tubes are often thought to be a consequence of adaptive specialization towards pollinator morphology. We explore floral tube length evolution within Tritoniopsis revoluta (Iridaceae), a species with considerable geographical tube length variation. We ask whether tube lengths of T. revoluta populations are associated with pollinator proboscis lengths, whether floral divergence occurs in the presence of different pollinators and whether floral convergence oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 59 publications
1
53
0
Order By: Relevance
“…Inferences about evolutionary processes have traditionally been made based on the observed interspecific variance of phenotypes (Darwin, ). Phenotypic diversity accumulated at the intraspecific level is also important to consider for a better understanding of processes behind geographical differentiation and adaptation, and to establish a connection between micro‐ and macroevolution (Roitberg et al, , Anderson, Ros, Wiese, & Ellis, , e.g. Bertin, Ruiz, Figueroa, & Gouin, , Jaffe, Campbell‐Staton, & Losos, , Tsuboi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Inferences about evolutionary processes have traditionally been made based on the observed interspecific variance of phenotypes (Darwin, ). Phenotypic diversity accumulated at the intraspecific level is also important to consider for a better understanding of processes behind geographical differentiation and adaptation, and to establish a connection between micro‐ and macroevolution (Roitberg et al, , Anderson, Ros, Wiese, & Ellis, , e.g. Bertin, Ruiz, Figueroa, & Gouin, , Jaffe, Campbell‐Staton, & Losos, , Tsuboi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Models of the evolution of specialization that incorporate environmental heterogeneity and associative mating indicate that these variables can result in a decrease in gene flow between environments and contribute to speciation [7]. Anderson et al [41] examined pollinators in different parts of a plant species' range and found a close association between floral traits and the traits of the pollinators in the region but did not find strong evidence that these patterns greatly influenced gene flow and dispersal. Presumably, if selection pressures were consistent for generations, speciation could occur, yet pollinators may be too variable between years [57].…”
Section: (C) Range Extent Specialization and Diversificationmentioning
confidence: 99%
“…For example, if spatial heterogeneity is such that the abundance of a commonly used host changes rapidly over space (beta-diversity is high), this should accelerate the evolution of specialization [41]. Much of the work in this area is done with herbivorous insects, with some studies suggesting that generalization is positively associated with large range size [55] and others finding cases where a specialist can have a much larger range if its host species is widespread [56].…”
Section: (C) Range Extent Specialization and Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…One striking example of community level patterns shaped by species interactions is the phenotypic convergence of mutualistic partners. Phenotypic convergence emerges in different mutualistic interactions such as plant-pollinator interactions (Anderson et al, 2014), plant-seed disperser interactions (Jordano, 1995), cleaning symbiosis in marine ecosystems (Stummer et al, 2004) and Müllerian mimicry,in which the per-capita predation risks of unpalatable individuals from different species with similar warning signals decay because they share costs of predators learning warning signals (Müller, 1879;Kapan, 2001;Ruxton et al, 2004;Meyer, 2006;Rowland et al, 2007;Elias et al, 2008). There are theoretical and empirical evidences that reciprocal selection imposed by mutualism can result in convergence between species (Guimaraes Jr et al, 2011;Thompson, 2006;Marek & Bond, 2009;Nuismer et al, 2013;Pinheiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%